P11.17 Intensification of a shigellosis epidemic associated with sexual transmission between men: diagnoses of shigella flexneri and s. sonnei in england, 2004 to 2015. (13th September 2015) - Field, N; Childs, T; Jenkins, C; Simms, I; Gilbart, VL; Dallman, TJ; Mook, P; Crook, PD; Hughes, G
Abstract : Introduction: Although Shigellosis is often associated with travel to high incidence regions, outbreaks of Shigella flexneri and S. sonnei associated with sexual transmission between men have been reported in the UK, Australia and elsewhere. We examined national trends in Shigella spp. diagnoses to explore the evidence for on-going sexual transmission of S. flexneri 3a and transmission of other Shigella serotypes or species between men in England. Methods: Local hospital laboratories submit presumptive strains of Shigella spp. to the Public Health England national reference laboratory for confirmation and typing. We report trends in diagnoses in men and women aged 16 to 60 years old, excluding cases with recent travel outside the UK. Results: Between January 2004 and February 2015, 53% (5, 051/9, 534) of Shigella spp. diagnoses made in England were not travel-associated, and diagnoses of S. flexneri 3a, S. flexneri 2a, and S. sonnei accounted for 78% of these cases. S. flexneri 3a diagnoses in men increased steadily from 2004 (3 cases) and peaked in 2013 (154 cases). Diagnoses of S. flexneri 2a in men followed a similar pattern, although increases emerged later, rising from 9 cases in 2004 to 220 cases in 2014. In 2010, diagnoses of S. sonnei in men began to exceed those in women (147 compared to 133 cases), and have since risen steadily in men (267 cases in 2014). Diagnoses in women remained low/stable throughout the study period, and the male to female gender ratios increased substantially, peaking in 2014 at 59:1, 17:1 and 3:1 for S. flexneri 3a, S. flexneri 2a, and S. sonnei . Conclusion: Surveillance data suggest an intensification of the shigellosis epidemic associated with sex between men in England. The timing and heterogeneity in species and serotypes implies separate introductions into the population. These data raise the possibility of new shigellosis outbreaks occurring elsewhere. Disclosure of interest statement: No pharmaceutical grants were received in the development of this study.